Development of novel 18-karat, premium-white gold bulk metallic glasses with improved tarnishing resistance. (15th February 2018) - Gross, Oliver; Eisenbart, Miriam; Schmitt, Lisa-Y.; Neuber, Nico; Ciftci, Lamia; Klotz, Ulrich E.; Busch, Ralf; Gallino, Isabella
Abstract: The 18kt gold-based bulk glass-forming composition Au49 Ag5.5 Pd2.3 Cu26.9 Si16.3 is modified in order to reduce its fast surface tarnishing caused by internal oxidation of Si, partitioning and fast out-diffusion of Cu and Au. By partially substituting Cu by the species Ga or Sn, the formation of Si as primary crystalline phase is facilitated and a distinct increase of the liquidus temperature is observed. It is found that a reduction of the Si content recovers the glass-forming ability of the novel Ga/Sn-containing alloys, reflected by an increasing reduced glass transition temperature, Trg, and a decreasing driving force for crystallization. This strategy is used to reduce the amount of Cu and Si, which are responsible for the fast surface tarnishing. Corrosion studies of the novel alloys reveal that the Cu release into an artificial saliva test solution is up to eight times lower than that of the mother alloy and the corrosion depth in artificial saliva is drastically lowered by 50% for the Ga-bearing alloys and by 80% for the Sn-bearing alloys. Graphical abstract: Image 1 Highlights: Partial substitution of Cu by Sn and Ga enabled a shift of the glass-forming region towards a lower Si content. The variation of the glass-forming ability is attributed to changes in the reduced glass transition temperature and in the driving force for crystallization. The novel compositions exhibit improved tarnishing resistance. The corrosion improvement goes beyond a simple reduction of out-diffusion due to the reduction of Cu and Si.